The impact of childhood maltreatment and parental styles on telomere length: the modulatory role of A118G - Chiara Pesca; Luisa Lo Iacono; Valeria Carola (European Journal of Psychotraumatology, 2025)
Background: Child maltreatment (CM) has been linked to both psychological and biological alterations across the lifespan. While extensive research has addressed the psychological consequences of early adverse experiences, the biological mechanisms – particularly those related to cellular aging – remain less understood. This study examined the effects of different CM types and perceived parenting styles on telomere length (TL), a recognized biomarker of cellular aging, in healthy young adults. Additionally, it explored whether the A118G polymorphism of the μ-opioid receptor gene (OPRM1) moderates these associations.Methods: A sample of 105 healthy young adults participated in the study. Participants completed validated self-report questionnaires assessing CM (Childhood Trauma Questionnaire – Short Form; CTQ-SF) and parental bonding (Parental Bonding Instrument; PBI). Saliva samples were collected for DNA extraction. TL was measured using Real-Time PCR, and A118G (rs1799971) genotyping was conducted via the TaqMan® protocol.Results: Individuals with a history of CM exhibited significantly shorter TL compared to those without such experiences. Specifically, TL showed significant negative correlations with emotional abuse and emotional neglect. Conversely, higher levels of parental care were positively associated with TL. Among parenting styles, the ‘affectionless control’ pattern – characterized by low care and high overprotection – demonstrated the strongest negative association with TL when reported for both parents. Moreover, the OPRM1 A118G polymorphism moderated the relationship between CM and TL: individuals with the A/A genotype were more vulnerable to TL shortening in the context of CM than G-allele carriers.Conclusion: These findings suggest that CM contributes to accelerated cellular aging and that parenting style, particularly affectionless control, exacerbates this effect. The moderating role of the μ-opioid receptor gene highlights the potential involvement of genetic factors in individual sensitivity to early-life adversity.